Perlindungan Hukum Bagi Pemegang Saham Yang Pailit Pada Perseroan Terbatas - Yahya, Christofer Chandra; Anggriawan, Teddy Prima (Jurnal Spektrum Hukum PMIH UNTAG Semarang, 2024)
Limited liability company is a subject of law protected by civil law. There is a separation of property between a limited company and its directors and shareholders. So the liability of the founder of the Limited Association is the limit of the capital deposited and does not include their personal property. This research method uses a juris-normative legal approach to study the norms that exist in positive law. The focus of the research is on the subjects of civil law, especially the Limited liability company (PT), where the responsibility of the founders of PT is limited only to the capital they invest in the company, which is clearly regulated in positive laws. In addition, in the context of a legal entity, a corporation may also be subject to a state of insolvency, which is governed by the Insolvency and Delayed Payment of Debt (CPPU) Act. However, in a case of pailit, there is no explicit legal protection for shareholders, either in the Act on Limited Entities or in the Bankruptcy Act and the CPPU Act. This suggests that the legal protection of the shareholder in the case of a pailit needs to be further examined and may require changes or additions to existing regulations.